PENGARUH LUMPUR SUNGAI TERHADAP PERTUMBUHAN DAN HASIL PADI TOLERAN ASAM-ASAM ORGANIK MERACUN GOLONGAN FENOLAT PADA SAWAH GAMBUT - Widodo Haryoko; M. Zulman Harja Utama (University of Prof. Dr. Hazairin, SH, 2020)
Experiments on the effect of river sludge on the growth and production of rice tolerant of organic acids poisoning phenolics in peat rice fields were carried out in Kenagarian Ketaping, sub-district Lembah Anai, district Padang Pariaman from October 2015 to January 2016 with the aim of knowing the interaction of river mud and acid-tolerant rice varieties organic acids phenolics in peat soil. The experiment was carried out in a randomized block design with the first factor being 3 river mud that were different locations, namely River Mud located 0.5 km from the estuary, river mud affected by sea water 2.0 km from the estuary, and river mud unaffected by eea water 4 km from the estuary, while the second factor is 3 rice varieties tolerant to organic acids tolerance toxic phenolics and 4 replicatons. The experimental results show that river mud can increase the growth and production of rice tolerant of organic acids to poison phenolics in peat rice fields with the highest production obtained in the Sunting Bungo Durian variety followed by Randah Kuning and then Cisokan Kuning varieties.